INNOVATION STRATEGY OPTIMIZATION ANALYSIS AND THE UTILIZATION OF E-COMMERCE SELLING KNOWLEDGE PRODUCTS BY DISABILITIES IN THE COVID-19 PANDEMIC PERIOD IN YOGYAKARTA CITY - Panji Kusuma Prasetyanto; Siti Afidatul Khotijah; Risma Wira Bharata (Jurnal Paradigma Multidisipliner (JPM), 2022)
This study aims to analyze the optimization of innovation strategies and the use of e-commerce by disabilities in selling products in the city of Yogyakarta and to determine the impact of the Covid-19 pandemic on the income of entrepreneurs in Yogyakarta City. The data used are secondary data and primary data in the form of producers in Yogyakarta City. Secondary data were obtained from the Office of Industry and Trade in Yogyakarta City and the primary data used were by conducting interviews with producers. This study uses two different test analysis tools to analyze the differences in the income of producers as a result of the Covid-19 pandemic. Based on the results of the study, it was found that there was a decrease in income that was felt by almost all producers by disabilities in Yogyakarta City, due to the Covid-19 pandemic and the lack of innovation in products and the lack of understanding of producers in using e-commerce as an effective marketing medium during the Covid-pandemic. 19. Keywords:, E-commerce, Innovation, Disabilities